Linear and cylindrical friction stir additive manufacturing (FSAM) of AA6061-T6 by consumable rods: metallurgical structure, wear, and corrosion properties - Kiani, Soheil; Mirsalehi, Seyyed Ehsan; Sahraei, Amirhossein (Welding in the world, 2024)
In the present research, the possibility of using friction stir deposition (FSD) for the additive manufacturing (AM) of aluminum parts has been evaluated and checked. For this purpose, consumable tool technique was used for depositing bulk samples in the shape of linear and cylindrical parts. The current friction stir additive manufacturing (FSAM) process was carried out through the deposition of AA6061-T6 consumable rods on a substrate of the same material. For each of the linear and cylindrical types, six samples were deposited in three layers using different production parameters. FSD tool speeds including rotational, linear, and vertical were the production parameters. To evaluate the additive manufactured parts, appearance, microstructure, hardness, wear properties, and corrosion resistance were inquired. The apparent appearance characteristics for both linear and cylindrical samples were continuous layers with sufficient thickness without cracks and cavities. In terms of microstructure characteristics, the hot plastic deformation during FSAM caused enormous grain refinement (~ 560%) through the dynamic recrystallization and decreasing the precipitate size (~ 31%) by the dissolution of precipitates in the matrix, compared with the AA6061-T6 consumable rods. These microstructural changes and production parameters were correlated with the amount of frictional heat generated during the process. In order to find this correlation, the change in amount of heat input by changing the production parameters and its effect on the microstructural characteristics were discussed. For both linear/cylindrical samples, by increasing the consumable tool rotational speed and decreasing its linear/vertical speed (increase in deposition time), the heat input increased, which led to more dissolution of precipitates (decreasing their size) and grain growth (reduction of grain boundaries as the preferred precipitation sites). Decreasing the precipitate size and precipitate content reduced the three-body wear mechanism and lowered the corrosion prone areas, which improved the wear and corrosion properties, respectively. Although the dissolution of precipitates reduced the hardness of samples compared to the hardness of consumable rods (AA6061-T6), the enormous grain refinement caused by FSAM compensated this deficiency. Finally, the properties of additive manufactured parts are as follows: relatively good hardness (~ 60 HV), excellent wear rate (about 3 µgr/N.m), low friction coefficient (0.6–0.8), and excellent corrosion rate (less than 5 mpy).